BREAKING THE ENTREPRENEURIAL GROWTH BARRIER: STARTUP STRATEGIES THAT SCALE SMARTER - A Suryanarayana; Aluvala Ravi, (International Journal of Advances in Business and Management Research (IJABMR), 2025)
This paper examines the complex and ambivalent challenges and opportunities associated with the scale of entrepreneurial ventures, providing a strategic framework around the theme of breaking the entrepreneurial growth barrier: startup strategies that scale smarter. The goal is to critically review the theoretical foundations of startups' scale-ups in ecosystems, as well as to present strategic levers for accelerating responsible and sustainable growth. Utilizing cross-disciplinary theoretical frames in strategic management, innovation, and entrepreneurial leadership, this paper is designed as a narrative-based analytical treatment to converge insights from established models and emergent thought leadership. The main contribution of this research is a categorization of "smart scaling strategies," including agility-focused models, resource leveraging means, ecosystem takeover, and adaptable market position. These tactics are introduced as an extendable and context-responsive approach, which is particularly useful for early-stage founders, incubators, and policymakers. This paper offers value by synthesizing this literature to propose an organizing lens that connects entrepreneurial ambition to operational scalability—a heuristic guide as opposed to a prescriptive manual. As a non-empirical paper, the generalizations and empirical evidence of this paper are restricted, but it gains high-level conceptual clarity and practical predictability. Among its implications, this study is relevant for entrepreneurs attempting to move from survival to scale, ecosystem enablers adopting growth-supportive policies, and educators developing entrepreneurs’ mindsets. What is new is to reposition “scaling” not only as a growth target but as a strategic posture based on systemic alignment, resource wisdom, and timing accuracy. In the end, this paper contends that to scale smarter, ambition is not enough: it requires strategic consistency, contextual intelligence, and ongoing learning.